2018
DOI: 10.1097/md.0000000000013034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of hemoglobinopathies in a large ethnic Hakka population in southern China

Abstract: Thalassemia is an inherited autosomal recessive disorder with microcytic hypochromic anemia resulting from reduced or absent synthesis of 1 or more of the globin chains of hemoglobin. This study provided the insight into prevalence and molecular characterization of thalassemia in Hakka population. 14,524 unrelated subjects were included in our study from January 2015 to November 2017. All the subjects were detected by hematological analysis, hemoglobin electrophoresis analysis, and molecular diagnosis (gap-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Consistent with a previous report, we found that β 0 ‐thalassemia is more common than β + ‐thalassemia. The two most common β‐‐thalassemia mutations in the Lao PDR populations are codon 41/42 (‐TTCT) and codon 17 (A‐T) which are similar to those found in Thailand, China, and South Vietnam …”
Section: Discussionsupporting
confidence: 61%
“…Consistent with a previous report, we found that β 0 ‐thalassemia is more common than β + ‐thalassemia. The two most common β‐‐thalassemia mutations in the Lao PDR populations are codon 41/42 (‐TTCT) and codon 17 (A‐T) which are similar to those found in Thailand, China, and South Vietnam …”
Section: Discussionsupporting
confidence: 61%
“…Hemoglobin electrophoresis was used to analyze the percent of hemoglobin Hbs A, A2, F, and any abnormal hemoglobin variant. The children with low HbA2 (<2.5%) values were considered possibly α-thalassemia carriers, with high HbA2 (>3.5%) values were considered possibly β-thalassemia carriers, respectively (13).…”
Section: Hematological Analysismentioning
confidence: 99%
“…However, the frequency is higher than that of the average level of Guangdong province (0.36%, P < .05), that of the average level of the 7 provinces in southern region of the Yangtze River (0.33%, P < .05), and that of the average level of the 7 provinces in northern region of the Yangtze River (0.17%, P < .05). [11] In this study, Hb Q-Thailand (HBA1: c.223 G > C) was the most frequent Hb variant (0.17%, 17/10,285) in Shaoguan. All Hb Q-Thailand cases were associated with -a 4.2 thalassemia and showed slight microcytosis.…”
Section: Discussionmentioning
confidence: 64%